Perforation Of Descending Colon Caused By Tumor Infiltration : A Case Report - Andry Irawan; Adeline Adeline; Martinus H. N. P Linggo (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Introduction: Colorectal cancer is one of the most common cancer found in the gastrointestinal tract. This tumor is less commonly found on the descending part of colon and about 15 - 30 % can progress to obstruct the passage of the colon and invade other organs and may cause perforation which may show sign of peritonitis. The majority of perforation cases occur in patients with acute obstruction, only in a rare setting of colonic cancer cases due to penetration of the tumor mass through the intestinal wall. Clinical Presentation: A 34-year-old male came with pain on his whole abdomen area for 1 day and keeps on getting worse. On clinical examination There were sign and symptoms of peritonitis and during emergency laparotomy, we found perforation on descending colon caused by tumor infiltration and performed Left Hemicolectomy and Stoma at emergency settings.Conclusion: Perforation of descending colon caused by tumor infiltration is a rare case, Left hemicolectomy and stoma shows good results in emergency settings.